Influence of ureolytic bacteria (UB) on the engineering properties and microstructure behavior of interlocking compressed earth bricks (ICEB) - Migat Omer, Megat Mohamad Zamer (2017)
Interlocking Compressed Earth Brick (ICEB) are cement stabilized soil bricks that allow for dry stacked construction. This characteristic resulted to the quick process of building walls at the same time, it requires less skilled labour as the bricks are laid dry and can easily be locked into its place. However, there are still rooms for improving the interlocking bricks by increasing its durability. Many studies had been conducted in order to improve the durability of bricks using environmental friendly method. One of the methods is by adding a certain amount of bacteria into the bricks during its production. Bacteria in brick induced calcite precipitation (calcite crystals) to cover the voids continuously. Ureolytic Bacteria (UB) is used in this study as a partially replacement of limestone water by varying the percentage at 1% UB, 3% UB and 5% UB. Enrichment process is done at soil condition to ensure the survivability of UB in ICEB environment. This research also evaluates the effect of UB in improving the engineering properties of ICEB and analyze the microstructure and morphology of UB in ICEB. Dimensional, compressive strength, water absorption and carbonation tests are performed for engineering properties, whereas X-ray fluorescence (XRF), Scanning electron microscopy (SEM) and X-ray diffraction (XRD) are analyzed for microstructure testing. The production of ICEB is carried out at Iryas Inc. (M) Sdn Bhd Industry at Sedenak, Johor and all test are conducted at Universiti Tun Hussein Onn Malaysia (UTHM) laboratory. The results for the engineering properties and microstructure analysis are compared with the control sample. It had been shown that the addition of 5% UB in ICEB indicated positive results in improving the ICEB properties by 15.25% increment in strength, 14.72% reduction in initial water absorption, 14.68% reduction in water absorption and 15.89% reduction of carbonation depth as compared with the control sample. Precipitation of calcium carbonate (CaCO3) in form of calcite can be distinguished clearly in microstructure analysis. As a conclusion, addition of 5% UB in ICEB promoted the highest increment in compressive strength and the lowest reduction in water absorption as compared with the other UB percentages.